Dietary Polyphenols Targeting Arterial Stiffness: Interplay of Contributing Mechanisms and Gut Microbiome-Related Metabolism - De Bruyne, Tess; Steenput, Bieke; Roth, Lynn; De Meyer, Guido R Y; Santos, Claudia Nunes Dos; Valentová, Kateřina; Dambrova, Maija; Hermans, Nina (Nutrients, 2019)
Increased arterial stiffness is a degenerative vascular process, progressing with age that leads to a reduced capability of arteries to expand and contract in response to pressure changes. This progressive degeneration mainly affects the extracellular matrix of elastic arteries and causes loss of vascular elasticity. Recent studies point to significant interference of dietary polyphenols with mechanisms involved in the pathophysiology and progression of arterial stiffness. This review summarizes data from epidemiological and interventional studies on the effect of polyphenols on vascular stiffness as an illustration of current research and addresses possible etiological factors targeted by polyphenols, including pathways of vascular functionality, oxidative status, inflammation, glycation, and autophagy. Effects can either be inflicted directly by the dietary polyphenols or indirectly by metabolites originated from the host or microbial metabolic processes. The composition of the gut microbiome, therefore, determines the resulting metabolome and, as a consequence, the observed activity. On the other hand, polyphenols also influence the intestinal microbial composition, and therefore the metabolites available for interaction with relevant targets. As such, targeting the gut microbiome is another potential treatment option for arterial stiffness.
Keywords: dieta; střevní mikroflóra; polyphenol biotransformation; polyfenoly; Vascular Stiffness; Gastrointestinal Microbiome; Polyphenols; analýza potravin; polyphenols; arterial stiffness; zvířata; Humans; autophagy; Food Analysis; gut microbiome; Diet; aging; anti-inflammatory; antioxidant; lidé; tuhost cévní stěny; Animals